The effect of implant supported mandibular oversentures lined with resilent liners on the muscular activity of completely edentulous patients : Electromyographic study - Ahmed Mohamed Abdelazeim Lashin; Amal Rekaby Taha; Azza Farahat Metwally (Cairo : Ahmed Mohamed Abdelazeim Lashin, 2013)
The aim of the present study was to evaluate the effect of resilient denture liner in implant tissue-suppored mandibular overdentures on the masticatory muscles activity of completely edentulous patients. Twelve completely edentulous male patients were randomly selected and equally divided into two groups. Both groups were rehabilitaed two implant tissue-suppoprted mandibular overdentures. However, group (I) patients had received two-implant and tissue-supported mandibular overdentures without resilient denture lining material and group(II) patients had received two-implant and tissue-supported mandibular overdentures lined with resilient denture lining material
Thesis (M.Sc.) - Cairo University - Faculty of Oral and Dental Medicine - Department of Prosthodontics
Issued also as CD
Keywords: Implant-overdentures; Resilient denture liners; Surface Electromyography